The Dynamics and Implementation of PT Kaltim Prima Coal’s CSR Programs in Advancing the Attainment of SDG 15 - Ivon Christiana Kadang; Bambang Shergi Laksmono (Global Writing Academica Researching and Publishing, 2025)
Coal mining activities in East Kalimantan Province provide a significant economic contribution, yet simultaneously triggering massive deforestation that threatens biodiversity. This research aims to analyze the dynamics and implementation of Corporate Social Responsibility (CSR) programs at PT Kaltim Prima Coal (KPC) in advancing the attainment of Sustainable Development Goals (SDG) 15 concerning Life on Land in Kutai Timur Recency. Employing a descriptive qualitative method with a purposive sampling technique, data were collected through observation, semi-structured interviews and documentation studies involving the company, local communities and local government agencies. The analysis was conducted using Triple Bottom Line (TBL) theory, SDG 15 framework, CSR theory and the Ecological Perspective. The findings indicate that PT KPC has integrated SDG 15 into its business strategy through the principle of Beyond Compliance, moving beyond mere regulatory obedience. Technical implementation focuses on restoring post-mining land to a safe, stable and productive condition through topsoil salvage and arboretum development, which has successfully reintroduced endemic fauna, signaling ecological recovery. A key finding of this research demonstrates an interdependent synergy between Environment and External Affairs division, where the technical requirement of 35.000 seedlings per month for reclamation was transformed into an economic empowerment program by involving local communities as strategic partners, thus supporting Target 15.c. Furthermore, the company successfully transformed environmental risk into sustainability assets, such as utilizing mining voids for municipal clean water (PDAM) and developing integrated cattle farming (PESAT) on reclaimed land. The study concludes that the successful achievement of SDG 15 is highly dependent on the balance between Planet, Profit and People pillars. Although persistent challenges in shifting community dependency patterns towards self-reliance, the strategic integration of CSR programs with the Regional Development Plan (RPD) and the legal assurance provided by the Mine Closure Plan (RPT) is essential for creating shared value and ensuring community economic independence after mining operations cease.